On the thinking of Traditional Chinese Medicine nursing talents cultivation based on the Traditional Chinese Medicine Nursing Inheritance Studio (基于中医护理传承工作站建设浅谈中医护理传承人才培养) - ZHANG Xuejian (张雪键); TANG Ling (唐玲); ZHANG Dahua (张大华); ZHANG Jing (张敬); LIU Jing (刘静); CUI Yangfang (崔杨芳) (中西医结合护理)
In recent years, more and more attention has been paid to the development of Traditional Chinese Medicine(TCM) nursing and strengthened the construction of TCM nursing talents cultivation. Innovating the training model of TCM nursing talents, accelerating the training speed of TCM nursing talents, and improving the quality of TCM nursing talents are important contents to promote the development of TCM nursing. The Inheritance Studio of Famous Traditional Chinese Medicine Experts is an important platform and carrier for learning, inheriting, researching and popularizing famous experts, academic ideas and clinical experience, and cultivating TCM talents with characteristic expertise. Combined with its own characteristics, the Third Affiliated Hospital of Beijing University of Chinese Medicine has carried out a series of TCM inheritance talents around the construction and innovation of Feng Yunhua Traditional Chinese Medicine Nursing Inheritance Studio, actively explored and summarized experience, and achieved good results. (近年来国家对中医护理发展日益重视, 不断加强对中医护理人才队伍的建设。创新中医护理人才培养模式、加快中医护理人才培养速度、提高中医护理人才培养质量是推进中医护理人才队伍建设的重要内容。而名老中医药专家传承工作室是学习继承和研究推广名老专家和学术思想与临床经验、培养具有特色专长的中医人才的重要平台和载体。本院结合自身特色, 围绕“冯运华中医护理传承工作站”建设创新开展了一系列中医传承人才的培养工作, 积极探索、总结经验, 取得了良好效果。)